Management of Child Development Center of Educational Administrators Sub-district Administration Organization in Nonthaburi Province - ศรีลับซ้าย พิมพ์พิชชา (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The purposes of this research were to; 1) study the management of child development center regulated by Subdistrict Administration Organization in Nonthaburi, and 2) compare the administrators’ opinion towards the management of Child Development Center regulated by educational administrators of SAO in Nonthaburi. The samples consisted of 169 people selected by random simple sampling method and categorized by gender, age, educational background, position, and experiences. The samples of this study were mayors, deputies, administrators and teachers of Child Development Centers managed by SAO in Nonthaburi. The data were collected by questionnaire; descriptive statistics used in this study were frequency, percentage, average, standard deviation, t-test, One-way ANOVA. The research findings were as follows: Management of Child Development Center organized by education administrators of SAO in Nonthaburi is in excellent level in overview. From the result on comparison level of attitudes toward management of Child Development Center of educational administrators classified by position, it showed significantly statistical differences at .05 on point of views on overall aspects, budget management, and general management.